2020
DOI: 10.3390/molecules25102380
|View full text |Cite
|
Sign up to set email alerts
|

Ras and Wnt Interaction Contribute in Prostate Cancer Bone Metastasis

Abstract: Prostate cancer (PCa) is one of the most prevalent and malignant cancer types in men, which causes more than three-hundred thousand cancer death each year. At late stage of PCa progression, bone marrow is the most often metastatic site that constitutes almost 70% of metastatic cases of the PCa population. However, the characteristic for the osteo-philic property of PCa is still puzzling. Recent studies reported that the Wnt and Ras signaling pathways are pivotal in bone metastasis and that take parts in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 164 publications
(172 reference statements)
1
18
0
1
Order By: Relevance
“…For GO term analysis, we found that the enriched cellular components were important for metastasis and neuronal development (extracellular matrix and neuron projection, Figure 6 B,C). A similar result was found by the KEGG pathway analysis ( Figure 6 D): Extracellular matrix (ECM) receptor interaction, cell adhesion, and molecular and wingless-related integration site (Wnt) signaling pathways are very important for metastasis [ 19 , 20 , 21 ], while neuroactive ligand–receptor interaction is critical for neuronal development. In addition, some studies have reported that calcium signaling pathways and tumor necrosis factor (TNF) signaling pathways are very important for tumorigenesis and the epithelial–mesenchymal transition (EMT) of PCa [ 22 ].…”
Section: Resultssupporting
confidence: 77%
“…For GO term analysis, we found that the enriched cellular components were important for metastasis and neuronal development (extracellular matrix and neuron projection, Figure 6 B,C). A similar result was found by the KEGG pathway analysis ( Figure 6 D): Extracellular matrix (ECM) receptor interaction, cell adhesion, and molecular and wingless-related integration site (Wnt) signaling pathways are very important for metastasis [ 19 , 20 , 21 ], while neuroactive ligand–receptor interaction is critical for neuronal development. In addition, some studies have reported that calcium signaling pathways and tumor necrosis factor (TNF) signaling pathways are very important for tumorigenesis and the epithelial–mesenchymal transition (EMT) of PCa [ 22 ].…”
Section: Resultssupporting
confidence: 77%
“…A study has reported that the Ras signaling pathway activates the tumor-related fibroblast and stimulates the proliferation of cancer cell [40]. Another study found that Ras signaling may participate in the process of prostate cancer metastasis to bone via interaction with Wnt signaling [41]. Proteoglycan is a type of biomacromolecule comprising a protein core and glycosaminoglycan.…”
Section: Discussionmentioning
confidence: 99%
“…KLF5 was also identified as target and inhibited by miR-21 at both mRNA and protein level [48]. Increased PCa cell migration and invasion in vitro as well as xenograft tumor growth by overexpression of miR-21 were confirmed [48,101] Consequently, miR-21 has been proposed as a potential diagnostic biomarker, as well as a therapeutic target for PCa [49,106]. However, its potential as a biomarker should be viewed with caution due to some controversial observations [45][46][47] The lack of reproducibility could be attributed to the diversity of patient cohorts, sample processing, measurement techniques and data analysis [107,108].…”
Section: Metastasis-related Mirnas With Conflicting Evidence 61 Mir-21mentioning
confidence: 97%
“…Most recently, Kim et al demonstrated the anti-cancer potential of anti-miR21, which blocks the tumor suppressor PTEN. They presented the modified locked nucleic acid (LNA) and poly nucleic acid (PNA)-type anti-miR21 and its therapeutic efficacy in vitro and in a murine PCa model, which showed reduced bone metastasis formation upon treatment [106]. Although miR-21 is thought to possess oncogenic properties due to its ability to negatively modulate PTEN and its knockdown reversed the malignant phenotype in several tumor models, the therapeutic potential of miR-21 for PCa is still questionable due to conflicting literature.…”
Section: Therapeutic Approaches Based On Mirna Regulationmentioning
confidence: 99%